In vivo Lineage-tracing Studies in a Cancer Stem Cell Population in Neuroblastoma - Danielle Hsu (Maiden name: Danielle M. Patterson); Jason Shohet; Eugene Kim (Bio-Protocol, 2014)
Tumors are comprised of heterogeneous subpopulations that may exhibit differing capacity for differentiation, self-renewal, and tumorigenicity. In vivo lineage-tracing studies are a powerful tool for defining the role of tumor subpopulations in tumor growth and as targets for therapeutic agents. This protocol describes using a neuroblastoma cancer cell line transduced with two different fluorescent proteins (GFP and tdTomato) to track the specific contributions of cells expressing the GCSF receptor (CD114+) or not (CD114-) on tumor growth in vivo.